An evaluation of the implementation of the normative objectives set for Environmental Management Frameworks in selected case studies in Gauteng and the Northwest Province, South Africa - Van Wyk, Marthinus Wessel (Department of Environmental and Geographical Science, 2015)
Includes bibliographical references (p. 78-87).